Localization, Gene Expression, and Functions of Glutamine Synthetase Isozymes in Wheat Grain (Triticum aestivum L.) - Wei, Yihao; Xiong, Shuping; Zhang, Zhiyong; Meng, Xiaodan; Wang, Lulu; Zhang, Xiaojiao; Yu, Meiqin; Yu, Haidong; Wang, Xiaochun; Ma, Xinming (Frontiers in Plant Science, 2021)
Glutamine synthetase (GS) plays a major role in plant nitrogen metabolism, but the roles of individual GS isoforms in grains are unknown. Here, the localization and expression of individual TaGS isozymes in wheat grain were probed with TaGS isoenzyme-specific antibodies, and the nitrogen metabolism of grain during the grain filling stage were investigated. Immunofluorescence revealed that TaGS1;1, TaGS1;3, and TaGS2 were expressed in different regions of the embryo. In grain transporting tissues, TaGS1;2 was localized in vascular bundle, TaGS1;2 and TaGS1;1 were in chalaza and placentochalaza, TaGS1;1 and TaGS1;3 were in endosperm transfer cells, and TaGS1;3 and TaGS2 were in aleurone layer. GS exhibited maximum activity and expression at eight days after flowering (DAF) with peak glutamine content in grains; from then, NH4+ increased largely from NO3- reduction, glutamate dehydrogenase (GDH) aminating activity increased continuously and the activities of GS and glutamate synthase (GOGAT) decreased, while only TaGS1;3 kept a stable expression in different TaGS isozymes. Hence, GS-GOGAT cycle and GDH play the different roles in NH4+ assimilation of grain in different stage of grain development; TaGS1;3, located in aleurone layer and endosperm transfer cells, plays a key role in Gln into endosperm for gluten synthesis. At 30 DAF, grain amino acids are mainly transported from maternal phloem.